2020
DOI: 10.1177/0300060519896144
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum exosomal miR-320a expression is an unfavorable prognostic factor in patients with hepatocellular carcinoma

Abstract: Objective Circulating microRNAs (miRNAs) have promising potential as diagnostic or prognostic biomarkers for hepatocellular carcinoma (HCC). This study aimed to analyze the clinical significance of serum exosomal miR-320a expression in patients with HCC. Methods A total of 104 patients with HCC, 55 patients with chronic liver disease (CLD), and 50 healthy volunteers were enrolled. Serum exosomal miR-320a levels were measured by quantitative reverse-transcriptase polymerase chain reaction and compared among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In a cohort of 59 HCC patients, authors found a correlation between tumor recurrence after liver transplantation and a higher level of miR-718 [ 60 ]. Similar signals were detected after liver resection and other exosomal miRNAs: high levels of miR-665 or low levels of miR-638 and miR-320a were identified as predictors of poor survival [ 61 , 63 , 66 ]. In a cohort of 79 HCC patients of different stages receiving various treatments, Lee et al focused on two candidates: a miRNA (miR-21) and a long non-coding RNA (lncRNA) (lncRNA-ATB).…”
Section: Introductionmentioning
confidence: 68%
“…In a cohort of 59 HCC patients, authors found a correlation between tumor recurrence after liver transplantation and a higher level of miR-718 [ 60 ]. Similar signals were detected after liver resection and other exosomal miRNAs: high levels of miR-665 or low levels of miR-638 and miR-320a were identified as predictors of poor survival [ 61 , 63 , 66 ]. In a cohort of 79 HCC patients of different stages receiving various treatments, Lee et al focused on two candidates: a miRNA (miR-21) and a long non-coding RNA (lncRNA) (lncRNA-ATB).…”
Section: Introductionmentioning
confidence: 68%
“…In another study, a machine learning based score (“HCC classifier”) with 8 lncRNAs markers showed very promising AUCs (0.953 in training cohort, 0.983 in validation cohort and 0.963 in testing cohort) [ 171 ]. Several other researchers focused their attention on exosomal miRNAs [ 173 , 174 , 175 , 176 , 177 ]. Some studies found similar diagnostic accuracies for AFP and EVs miRNAs [ 173 , 175 ], while others demonstrated the superiority of the latter [ 174 , 176 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…A lower number of studies investigating EVs in the prognostic field are available, and most of them focused on the evaluation of exosomal miRNAs, in particular after surgical therapies (liver resection or liver transplantation) [ 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. The only miRNA included in more than one study was miR-21, and its high levels have been repetitively associated with increased risk of disease progression and poorer survival [ 182 , 184 , 185 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies demonstrated that LINC00963 as a sponge of miRNA was involved in tumor growth [4][5][6]. miR-320a is located on human chromosome 8p21.3 and closely related to disease progression, tumor invasion and metastasis [7][8][9][10], the expression of which could be regulated by different lncRNA in different disease [8,11,12]. The endoplasmic reticulum (ER) stress or autophage-related proteins are correlated with worse overall survival of DLBCL patients and affected response of DLBCL to chemotherapy [13,14].…”
Section: Introductionmentioning
confidence: 99%